Changes in risk perceptions before and after nuclear accidents: Evidence from Japan. Issue 55 (January 2016) - Nishikawa, Masashi; Kato, Takaaki; Homma, Toshimitsu; Takahara, Shogo
Highlights: We assess net costs/benefits perceived by residents surrounding nuclear plants. Survey data before and after nuclear accidents are quantitatively analyzed. Health risks are considered more worrisome than the probability of accidents. Japan's nuclear policy should aim to change people's perceptions of nuclear power. Policy measures may include enhanced evacuation planning and post-disaster support. Abstract: We quantitatively analyzed changes in residents' perceptions of the net benefits derived from the Kashiwazaki–Kariwa nuclear power station (KK) before and after the accident at the Fukushima Daiichi plant (FD) following the Great East Japan Earthquake on March 11, 2011. Employing data from two surveys—conducted in January 2010 and December 2011 before and after FD accident, respectively—we found that KK's perceived net benefits declined after the FD accident. This decline resulted from changes in respondents' relative weightings of KK's costs and benefits rather than heightened expectations of future nuclear accidents. We also found that residents living near nuclear facilities are more concerned about health risks from nuclear accidents than the likelihood of such accidents caused by human error. We suggest that a more effective policy entails changing people's relative weighting of nuclear facilities' costs and benefits by protecting lives through enhanced evacuation planning and post-disaster support for rehabilitation, although Japan's current nuclear power policy aims to assuage people's risk perceptions by reducing the probability of nuclear accidents to zero.